“A life without a supervisor is like a seed that never grows”: Students’ Experiences of Undergraduate Nursing Research Supervision - Cyruz P. Tuppal; Alejandro C. Nonog Jr.; Shanine Mae P. Tuppal; Mark Donald C. Reñosa; Marina Magnolia G. Ninobla; Mary Nellie T. Roa; Christian S. Tu (Nurse Media Journal of Nursing, 2022)
Background: Undergraduate research is an inquiry or investigation conducted by students who develop an original intellectual or creative contribution to the discipline. However, little is known within the Philippine context that explores undergraduate nursing research experience and supervision.Purpose: This study illustrated the students’ lived experiences of undergraduate research supervision using transcendental phenomenology.Methods: This study made use of transcendental phenomenology. Thirty students enrolled full-time in a nursing research course during the academic year (AY) 2019-2020, and AY 2020-2021 were purposively sampled. These students completed their research projects as required for the nursing research course and were supervised by a mentor. Each participant underwent an in-depth one-on-one interview, of which the responses were transcribed and analyzed based on the modified Stevick-Colaizzi-Keen method.Findings: From the thirty-nine significant statements carefully reviewed and clustered into meaning units, three themes emerged, namely (a) re-capturing tripartite challenges in doing research, (b) re-cultivating quintessential requisites in doing research, and (c) re-envisioning the future ahead. These themes provided textural and structural descriptions that intuitively integrate into the essence of the lived experience of being supervised in undergraduate research.Conclusion: Undergraduate research supervision resonates with the mutual exchange of novel ideas in a dialogical encounter, collective learning, and participatory-in-action where sciencing and caring thinking is imbued to develop critical thinking, inquisitiveness, and caring intuitiveness.